UNJUK KERJA MESIN PENCACAH SAMPAH - Juardin, Juardin; Sudia, Budiman; Imran, Al Ichlas (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2017)
The aim of this research is to know the difference of time and of the result of plastic waste enumeration on blade before and after modification to material weight of 250gr, 500gr, and 750gr. This study compared the length of time and of the enumeration results on the blades before they were modified and after modified. Variations in waste weight were 250gr, 500gr, and 750gr. The results showed that the percentage comparison of the length of the process of enumerating plastic waste before modification with the weight of 250gr resulted in enumeration time for 35 seconds, so that the effective capacity of the tool was 25.71 kg / hour. For weight of garbage equal to 500gr produce enumeration time for 126 second, with tool capacity 14,28 kg/hour. While the weight of garbage 750gr produce enumeration time for 192 seconds, with the effective capacity of the tool of 14.06 kg/hour. For the conditions after modification of the blades, the weight of the waste of 250gr resulted in an enumeration time of 80 seconds, in which the effective capacity of the apparatus was 11.25 kg/hr. For the weight of garbage of 500gr was resulted enumeration time for 255 seconds, where the effective capacity of the tool obtained was 7.05 kg/hour. While the weight of 750gr garbage generates the enumeration time for 401 seconds, where the effective capacity of the tool obtained of 6.73 kg/hour. The quality of enumeration of plastic waste on the blades before the modification was still not chopped properly, while the results of plastic waste debris on the blades after modified has been chopped well but the results were not irregular. Keywords: Plastic waste, chopping machine, enumeration time, size of enumeration result.